Speculative bubbles and crashes: Fundamentalists and positive-feedback trading - Po-Keng Cheng; Young Shin Kim (Cogent Economics & Finance, 2017)
In this paper, we develop and examine a simple interactive agent-based model, where the distribution of returns generated from the model takes into account two stylized facts about financial markets： fat tails and volatility clustering. Our results indicate that the risk tolerance of fundamentalists and the relative funding rate of positive-feedback traders versus fundamentalists are key factors determining the path of price fluctuations. Fundamentalists are more able to dominate the market when they are more willing than positive-feedback traders to take risks. In addition, more crises occur as positive-feedback traders face higher funding costs compared to fundamentalists. Our model suggests that fundamentalists cause heavier tails, and positive-feedback traders cause the formation of speculative bubbles. Our model also indicates that traders' attitudes toward risk vary across time and market. The generally low level of risk bearing by fundamentalists could explain the frequent occurrence of bubbles.
Keywords: D49; G10; 330; noise traders; positive-feedback traders; fundamentalists; rational bubbles; speculative bubbles; wealth effect; heavy tails